2010
DOI: 10.3109/08820538.2010.518542
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Imaging of Corneal Inflammation: New Tools for Clinical Practice and Research

Abstract: Purpose Infectious and inflammatory corneal diseases are a major cause of blindness. To date, assessment of corneal inflammation, has only been possible by slit-lamp biomicroscopy. The purpose of this study is to review the current state of imaging technologies enabling in vivo imaging of inflammation in the cornea. Methods Literature review of peer-reviewed articles on in vivo imaging modalities. Results Current means of diagnosis and treatment follow-up for immune and infectious keratitis are limited to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 52 publications
(60 reference statements)
2
33
0
1
Order By: Relevance
“…63 IVCM allows the study of corneal cells, nerves and the immune cells and their various interactions in ocular and systemic diseases. 16,64 IVCM has been utilized to study nerve changes in various conditions including normal eyes, keratoconus, dry eye disease, 65 contact lens wear, neurotrophic keratopathy, 66 infectious keratitis, 67 post refractive surgery, among others. 16,63,64,68 Moreover, IVCM has enabled us to study the regenerative changes of the corneal nerves and correlation with corneal sensation.…”
Section: Assessment Of Ocular Surface Painmentioning
confidence: 99%
“…63 IVCM allows the study of corneal cells, nerves and the immune cells and their various interactions in ocular and systemic diseases. 16,64 IVCM has been utilized to study nerve changes in various conditions including normal eyes, keratoconus, dry eye disease, 65 contact lens wear, neurotrophic keratopathy, 66 infectious keratitis, 67 post refractive surgery, among others. 16,63,64,68 Moreover, IVCM has enabled us to study the regenerative changes of the corneal nerves and correlation with corneal sensation.…”
Section: Assessment Of Ocular Surface Painmentioning
confidence: 99%
“…Intravital imaging in mouse models has been developed to directly visualize and measure neutrophil migration and function in specific organs after acute tissue damage. These models mainly focus on peripheral tissues in mice that are amenable to imaging, including the cornea 147 , ear dermis 7,68 and cremaster muscle 110,148150 . Other methods create “windows” through which immune cell infiltration can be visualized in the brain 151 and lungs 152 .…”
mentioning
confidence: 99%
“…[12][13][14][15][16] These observations could be made for diabetic neuropathy, 12 infectious keratitis, 15 dry eye syndrome, 17,18 neurotrophic keratopathy, and contact lens use. 10,19 The utility of CCM as a surrogate marker for small-fiber injury has been explored in different neuropathies. [20][21][22][23] In a recent study, Tavakoli et al found that the corneal nerve fiber density (NFD) is significantly reduced in patients with SFN.…”
mentioning
confidence: 99%